(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article discusses the role and importance of phytotherapy in medicine. As we know, today, natural treatment is considered a guarantee of health in order to recover from the disease without complications and not to get the same disease again. In addition, information is given on the fact that phytotherapy is safe for human health, unlike drugs.